2013
DOI: 10.1111/ene.12226
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disorders in myotonic dystrophy type 2: a controlled polysomnographic study and self‐reported questionnaires

Abstract: Sleep quality in DM2 patients is poorer than in DM1 patients and controls. Sleep apnea is the most common sleep disorder in DM2 patients. Obstructive sleep apnea and sleep fragmentation may represent the main cause of EDS, whereas PLMS is a frequent finding in DM1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
23
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 18 publications
0
23
0
1
Order By: Relevance
“…However, RSWA and RBD has been described as a hypothetical compensatory and protective mechanism against OSA [13]. We hypothesize that SBMA may predispose to RSWA for its intrinsic neurodegenerative mechanisms, and that OSA may represent a compensatory trigger that may unmask a RSWA propensity as recently observed in myotonic dystrophy type 2 [14]. On the other hand, Huang et al [13] reported that patients with RBD and OSA not affected by neuromuscular diseases, presented shorter duration of apneas and hypopneas during REM than NREM sleep.…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…However, RSWA and RBD has been described as a hypothetical compensatory and protective mechanism against OSA [13]. We hypothesize that SBMA may predispose to RSWA for its intrinsic neurodegenerative mechanisms, and that OSA may represent a compensatory trigger that may unmask a RSWA propensity as recently observed in myotonic dystrophy type 2 [14]. On the other hand, Huang et al [13] reported that patients with RBD and OSA not affected by neuromuscular diseases, presented shorter duration of apneas and hypopneas during REM than NREM sleep.…”
mentioning
confidence: 64%
“…Furthermore, subjective evaluation of diurnal sleepiness showed a significant higher score of ESS without reaching pathological levels in SBMA patients, confirming the poor reliability of this scale with MSLT in OSA and neuromuscular disorders [5,14,15].…”
mentioning
confidence: 80%
“…We recently published a full PSG-controlled study of sleep and sleepiness in DM2 (PSG American Academy of Sleep Medicine type 2 followed by multiple sleep latency test and comprehensive subjective questionnaires) and compared our results to those obtained in DM1 and healthy controls. 3,4 We found impaired sleep efficiency in 12/12 patients with DM2, in association with OSA in 7/12 patients (58.3%). Interestingly, 6/12 patients with DM2 (50%) showed REM sleep without atonia (RSWA) with REM sleep behavior disorder (RBD) in 1/6, confirming REM sleep dysregulation in myotonic dystrophies.…”
mentioning
confidence: 70%
“…However, in our study, 1,6 we evaluated the occurrence of SDB in patients with DM2 by home-based cardiorespiratory monitoring, since SDB may worsen cardiorespiratory and cognitive functions, which are often impaired in these patients. Nevertheless, Romigi et al 3 raised an issue concerning the relationship between obstructive sleep apnea syndrome (OSAS) and RSWA; it would be interesting to evaluate if ventilatory treatment of OSAS in patients with DM2 could also be beneficial for RSWA and RBD if these conditions were pathologically related to OSAS as these authors suggest. Moreover, their study confirms that SDB is the most relevant sleep disorder in patients with DM2.…”
mentioning
confidence: 99%
“…Therefore, there is a growing evidence that unattended portable devices are useful in different clinical settings. [7][8][9] An experienced sleep technologist/ technician must apply the sensors. Manual scoring review of the raw data should be performed by board certified sleep specialists.…”
Section: Dear Editormentioning
confidence: 99%